Fertility Preservation in Women With Malignancy: Future Endeavors - Zeev Blumenfeld (SAGE Publishing, 2019)
The area of fertility preservation is constantly developing. To date, the only noninvestigational and unequivocally accepted methods for fertility preservation are cryopreservation of embryos and unfertilized oocytes. This article is one of several in a monogram on fertility preservation. The debate, pros and cons, and equivocal data on the use of GnRH analogues for fertility preservation are elaborated by 3 other manuscripts, in this monogram. A repeat of the arguments, pros and cons of this debatable issue, would be a repetition and redundancy of what is already included in this monogram. The subject of ovarian cryopreservation for fertility preservation is also elaborated by several other authors in this monogram. It is possible that, in the not too far future, the technologies of in vitro maturation of primordial follicles to metaphase 2 oocytes, and the "artificial ovary," will turn clinically available. These technologies may bypass the risk of resuming malignancy by autotransplantation of cryopreserved-thawed ovarian tissue in leukemia and diseases where malignant cells may persist in the cryopreserved ovarian tissue. We summarize here the suggested options for future endeavors in fertility preservation.